2019
DOI: 10.2478/subboec-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

The Inflation-Growth Relationship in SSA Inflation-Targeting Countries

Abstract: This paper investigates the relationship between inflation and economic growth for South Africa and Ghana using quarterly empirical data collected from 2001 to 2016 applied to the quantile regression method. For our full sample estimates we find that inflation is positively related with growth in Ghana at high inflation levels whilst inflation in South Africa exerts its least adverse effects at high inflation levels. However, when particularly focusing on the post-crisis period, we find inflation exerts negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…They concluded that the relationship between output growth and general prices is linear and negatively related in Ghana. For Mavikela, et, al, (2018) inflation has been directly linked with growth at high prices in Ghana from 2001 to 2016 by the use of quarterly empirical data.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the relationship between output growth and general prices is linear and negatively related in Ghana. For Mavikela, et, al, (2018) inflation has been directly linked with growth at high prices in Ghana from 2001 to 2016 by the use of quarterly empirical data.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…The CC-BY License | 118 majority of the literature has concluded on a negative relationship between some macroeconomic indicators such as inflation and GDP growth rate in Ghana at all levels (Enu et al, 2013). However, Mavikela et al, (2018) examined how inflation and economic growth are related in South Africa and Ghana and concluded on a positive effect of inflation on GDP growth in Ghana at a high inflationary level. Mbulawa (2015) also concluded on the positive effect of inflation on GDP growth in Botswana.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the studies that primarily focused on the relationship between inflation and economic growth, a negative relationship was found by Quartey (2010); Mamo (2012) and Gokal and Hanif (2004). However, some studies found that inflation has no impact on economic growth (Faria & Carneiro, 2001;Sidrauski, 1967;Svigir & Miloš, 2017) whilst Mavikela, Mhaka, and Phiri (2019) found that inflation is positively related to growth at high inflation levels in Ghana and Tobin (1965) established a positive impact of inflation on growth. These studies found different and inconclusive results with regard to the relationship between inflation and economic growth.…”
Section: Theoretical and Empirical Literaturementioning
confidence: 99%
“…To what level can the inflation rate be targeted so that economic growth can be further optimized. This question is important to be asked to provide an economic policy foundation that consistently supports the main development goals, namely community welfare (Carrera, 2017;Mavikela, Mhaka, & Phiri, 2018).…”
Section: Introductionmentioning
confidence: 99%